Ecological dihydrate gypsum-based waterproof inorganic water-based coating and preparation method thereof
By adding metakaolin and white silicate cement to dihydrate gypsum and carrying out hydration reactions to generate water resistance and gelling substances, the defects of dihydrate gypsum in water resistance and water resistance are solved, and its use as an effective bonding film forming agent for building coatings is realized, forming an ecological waterproof coating with excellent performance.
Patent Information
- Application Number
- CN202310732377.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-06-20
AI Technical Summary
Dihydrate gypsum has defects in water resistance and water resistance, resulting in its limited use in some applications and is difficult to use as an effective bonding film-forming agent for architectural coatings.
通过在二水石膏中添加偏高岭土和白色硅酸盐水泥,并在有水参与的情况下进行水化反应,生成具有耐水性和胶凝性的水钙沸石和水化硅酸钙等耐水物质,从而提高其在水中的稳定性和涂料的强度。
The water resistance and bonding performance of dihydrate gypsum have been improved, forming an ecological dihydrate gypsum-based waterproof inorganic water-based coating with excellent apparent performance and durability, suitable for waterproof coatings for buildings.
Smart Images

Figure BDA0004294605000000061 
Figure BDA0004294605000000071 
Figure BDA0004294605000000072
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation and application of inorganic water-based coatings, and in particular to an ecological dihydrate gypsum-based waterproof inorganic water-based coating and a preparation method thereof. Background Art
[0002] With the rapid development of the construction industry, gypsum building materials have been listed as a key development area of new building materials in my country. Gypsum is an easily mined gas-hardening material with many excellent properties. It consumes low energy during production and does not emit CO2 during the production process. 2 ; Gypsum has high hydration activity, rapid reaction and short hardening time. Its hardened body has good thermal insulation and sound absorption properties, good fire resistance, and micro-expansion after hardening. Gypsum products do not crack or hollow, and have good decorative properties. In addition, gypsum materials also have the characteristics of regulating indoor humidity, which can improve the comfort of housing. In the face of increasingly severe energy and environmental problems, gypsum is currently a green and environmentally friendly building material that has attracted much attention.
[0003] Due to the thermal insulation properties of gypsum, it is widely used in the field of fire retardant coatings. Gypsum is used as the basic material, and inorganic thermal insulation materials are added to it to prepare gypsum-based fire retardant coatings. Guo Liqin used gypsum slag cement and other materials to obtain thick steel structure fireproof and thermal insulation coatings ("Research on Gypsum Slag Cement-based Thick Steel Structure Fireproof and Thermal Insulation Integrated Coatings", Guo Liqin, Concrete and Cement Products, 2018). The equilibrium temperature of the coating is 380°C, and the thermal conductivity is 0.070W / (m·K), which has a good fireproof effect. Gypsum fire retardant coatings absorb heat at the beginning of water volatilization, followed by the decomposition of dihydrate gypsum crystal water, and finally the inorganic thermal insulation material absorbs heat. Various substances in the coating absorb heat, so it has good fireproof properties.
[0004] The fatal disadvantage of gypsum is that it has poor waterproof and water resistance, high water absorption and low softening coefficient. The reason why gypsum products are not water-resistant is because of the great solubility of dihydrate gypsum itself, the hydrophilicity of dihydrate gypsum and the capillary phenomenon caused by micropores absorbing water during the hydration process. Due to these reasons, the use of gypsum products in certain applications has been very limited so far. It is almost entirely used inside buildings, which greatly restricts its development and application.
[0005] Therefore, few scholars use gypsum as raw material to prepare waterproof architectural coatings. In the invention patent application with publication number CN111039643A, Jiang Xiaoyue et al. added a certain amount of active volcanic ash materials such as silica fume and metakaolin to anhydrous hard gypsum and high-strength semi-hydrated gypsum, thereby improving the mechanical strength and waterproof performance of the coating. However, anhydrous hard gypsum and semi-hydrated gypsum are obtained by high-temperature calcination and dehydration of dihydrate gypsum, and the hydration rate of semi-hydrated gypsum is too fast, and the construction time of the coating is short. So far, there has been no report on the direct use of dihydrate gypsum as a coating bonding film-forming agent. How to make dihydrate gypsum have bonding, water resistance and micro-expansion crack resistance, and give full play to its function as a bonding film-forming agent for architectural coatings is the key to the problem.
[0006] The dispersion medium of solvent-based paint is an organic solvent, and the emission of volatile organic compounds (VOC) is relatively high. The dispersion medium of water-based paint is water, and its film-forming substance is an inorganic component, and the emission of volatile organic compounds is almost zero. Compared with solvent-based paint, water-based paint is a green and environmentally friendly paint.
[0007] Therefore, after long-term experimental research by the inventor's team, the present application proposes to use dihydrate gypsum, metakaolin and white silicate cement as the main raw materials. In the presence of water, part of the dihydrate gypsum, metakaolin and white silicate cement undergo hydration reaction to generate water-resistant substances such as hydrated calcium zeolite and hydrated calcium silicate with water resistance and gelling properties. For details, see Figure 1 In the early stage of hydration, many smaller crystals are generated. The tiny crystals rely on gravity to bond each other at the contact points and form a spatial network structure. As hydration continues, the unstable coating on the surface of the particles begins to break and the hydration reaction accelerates. New and more stable hydrate crystals are precipitated from the saturated solution. These crystals continue to grow and rely on multiple gravitational forces to bond each other to form a tight structure. New crystals precipitated from the solution and hydrated calcium silicate gel continue to fill the space in the structure. These water-resistant gelling substances coagulate and harden, making the unreacted dihydrate gypsum and inorganic fillers firmly bonded together to form a water-resistant whole. See the SEM picture. Figure 2 , improving its stability in water and the strength of the coating, so dihydrate gypsum is used as an inorganic film-forming binder and filler for the coating. The film formed by adding a small amount of water-dispersible or water-soluble polymer powder binder has a barrier function, which helps to reduce the potential alkali-forming possibility of the coating, thereby obtaining excellent coating surface properties. Adding inorganic fillers can adjust the expansion rate, surface hardness and scrub resistance of the coating. Coarse particle fillers can also create the texture of the coating and improve the decorative performance of the coating. Summary of the invention
[0008] The present invention aims to provide an ecological dihydrate gypsum-based waterproof inorganic water-based coating and a preparation and use method thereof, and in particular to provide an ecological dihydrate gypsum-based waterproof inorganic water-based architectural coating whose main characteristics are waterproofness, green environmental protection and long service life.
[0009] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0010] The ecological dihydrate gypsum-based waterproof inorganic water-based paint of the present invention comprises the following raw materials in parts by weight: 10-55 parts of dihydrate gypsum, 10-55 parts of metakaolin, 10-40 parts of white silicate cement, 1-10 parts of polymer powder binder, 1-50 parts of filler, 0.1-0.5 parts of high-efficiency water reducing agent, 0.1-0.5 parts of defoaming agent, 0.1-0.5 parts of dispersant, 0.1-0.5 parts of leveling agent, 0.1-0.5 parts of anti-sagging agent and 0.1-0.5 parts of water retaining agent.
[0011] Preferably, the present invention comprises the following raw materials in parts by weight: 20-45 parts of dihydrate gypsum, 15-30 parts of metakaolin, 20-40 parts of white silicate cement, 2-6 parts of polymer powder binder, 5-25 parts of filler, 0.1-0.2 parts of high-efficiency water reducing agent, 0.1-0.3 parts of defoaming agent, 0.1-0.3 parts of dispersant, 0.1-0.2 parts of leveling agent, 0.1-0.3 parts of anti-sagging agent, and 0.1-0.3 parts of water retaining agent.
[0012] Further preferably, the present invention comprises the following raw materials in parts by weight: 30 parts of dihydrate gypsum, 20 parts of metakaolin, 30 parts of white silicate cement, 4 parts of polymer powder binder, 15 parts of filler, 0.15 parts of high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retaining agent.
[0013] According to actual needs, the ecological dihydrate gypsum-based waterproof inorganic water-based paint may further contain: 0-15 parts of pigment.
[0014] The main component of the dihydrate gypsum of the present invention is CaSO 4 ·2H 2 O, purity ≥90%, whiteness ≥80%, fineness ≥300 mesh, moisture content ≤1%.
[0015] The metakaolin of the present invention mainly comprises silicon dioxide and aluminum oxide, has a whiteness of ≥80%, a fineness of ≥500 meshes, and a moisture content of ≤1%. The kaolin calcined at 600-900°C is preferred.
[0016] The white silicate cement of the present invention has a fineness of ≥300 mesh, a whiteness of ≥80%, and a moisture content of ≤1%, preferably 42.5 or 52.5 white silicate cement.
[0017] The polymer powder binder described in the present invention is a composite of one or more of water-soluble polyvinyl alcohol, redispersible latex powder of vinyl acetate and ethylene copolymer, redispersible latex powder of ethylene, vinyl chloride and vinyl silicate terpolymer, and redispersible latex powder of vinyl acetate, acrylic acid ester and higher fatty acid vinyl ester terpolymer; the fineness of the polymer powder binder is ≥100 mesh, and the moisture content is ≤2%.
[0018] The high-efficiency water reducer of the present invention is a powder-type high-efficiency water reducer with a fineness of ≥100 mesh, and is preferably a polycarboxylic acid high-efficiency water reducer;
[0019] The defoamer is a powder defoamer with a fineness of ≥100 mesh, and preferably polyether modified silicon;
[0020] The dispersant is a powder type dispersant with a fineness of ≥100 mesh, preferably polyethylene oxide;
[0021] The leveling agent is a powder leveling agent with a fineness of ≥100 mesh, and is preferably polyether-modified polydimethylsiloxane;
[0022] The anti-sagging agent is a powder type anti-sagging agent with a fineness of ≥100 mesh, and is preferably polyamide wax powder;
[0023] The water retaining agent is a powder type water retaining agent with a fineness of ≥100 mesh, and is preferably hydroxypropyl methylcellulose.
[0024] The filler described in the present invention is an inorganic filler, which is one or a combination of two or more of quartz powder, wollastonite powder, sericite powder, talcum powder, heavy calcium carbonate powder or diatomaceous earth powder, preferably quartz powder, with whiteness ≥80%, fineness ≥600 mesh, and moisture content ≤1%.
[0025] The preparation method of the present invention comprises the following steps: uniformly mixing the formulated amounts of dihydrate gypsum, metakaolin, white silicate cement, polymer powder binder, inorganic filler, high efficiency water reducer, defoamer, dispersant, leveling agent, anti-sagging agent and water retaining agent, and then sealing and moisture-proof packaging for storage in a dry environment.
[0026] The method of use is: weigh the above-prepared coating, add an appropriate amount of clean water and mix evenly, control the viscosity of the slurry to 14-19s per 4 cups, stir evenly until there are no particles, and then it can be used. Ensure that the coating construction temperature is above 5°C, wet the wall with clean water, and then apply by brush, roller or spray, and apply 1-3 times as needed.
[0027] The beneficial effects are as follows:
[0028] 1. The main raw material of the present invention, dihydrate gypsum, is derived from natural minerals, has a simple production process, low energy consumption, and a more favorable price than calcined hemihydrate gypsum or anhydrous gypsum, which can greatly reduce costs.
[0029] 2. The present invention uses dihydrate gypsum as an inorganic film-forming binder and filler for the coating, thereby improving its stability in water and also improving the strength of the coating; the film formed by adding a small amount of water-dispersible or water-soluble polymer powder binder has a barrier function, which helps to reduce the potential alkali efflorescence of the coating, thereby obtaining excellent coating surface performance; adding inorganic fillers can adjust the expansion rate, surface hardness and scrub resistance of the coating, and the coarse particle filler can also create the texture of the coating and improve the decorative performance of the coating. The coating finally prepared has a smooth surface, a surface drying time of less than 2 hours, a contrast ratio of 0.94-0.96, a scrub resistance of more than 2000 times, and after 5 temperature-resistant cycles, the coating is intact, the stain resistance is less than 15%, and the water resistance, alkali resistance, artificial weathering resistance and other tests meet the qualified requirements. The coating has an intact appearance without powdering, discoloration or cracking. The pH of the paint slurry is 10, so there is no need to add antibacterial agents. It also has antibacterial effects and will not mold or discolor when used on exterior walls. The whiteness is greater than 85, so there is no need to add titanium dioxide pigment, which can reduce costs.
[0030] 3. The preparation method of the present invention is simple and easy to implement. The coating obtained has excellent performance and is excellent in texture, pencil hardness, adhesion, water resistance, alkali resistance, freeze-thaw resistance, long life, etc., and has high economic, environmental and social benefits. In addition, the coating is in powder form, has a long shelf life, and can be used after adding water and stirring evenly, which is in line with the future development trend of green and healthy architectural coatings; at the same time, due to the simple packaging and convenient transportation process, the packaging and transportation costs are greatly reduced, and it has performance and price advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the XRD spectrum of the hydration reaction products of dihydrate gypsum, metakaolin and white silicate cement.
[0032] Figure 2 This is the SEM image of the hydration reaction products of dihydrate gypsum, metakaolin and white silicate cement.
[0033] Figure 3 SEM images of the surfaces of dihydrate gypsum, metakaolin, white silicate cement, filler and polyvinyl alcohol coating. DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with the examples. However, these examples shall not be interpreted as limiting the scope of protection of the present invention. The experimental methods in the following examples that do not specify specific conditions shall be selected according to conventional methods and conditions, or according to the instructions for use of the product. The high-efficiency water reducer described in the following examples is a polycarboxylic acid high-efficiency water reducer; the defoamer is polyether-modified silicon; the dispersant is polyethylene oxide; the leveling agent is polyether-modified polydimethylsiloxane; the anti-sagging agent is polyamide wax powder; and the water retaining agent is hydroxypropyl methylcellulose.
[0035] Example 1: Ecological dihydrate gypsum-based waterproof inorganic water-based coating
[0036] Raw material ratio: 30 parts of dihydrate gypsum, 20 parts of metakaolin, 30 parts of white Portland cement, 4 parts of polyvinyl alcohol, 15 parts of quartz powder, 0.15 parts of high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0037] Example 2: Ecological dihydrate gypsum-based waterproof inorganic water-based coating
[0038] Raw material ratio: 20 parts of dihydrate gypsum, 25 parts of metakaolin, 30 parts of white Portland cement, 4 parts of polyvinyl alcohol, 20 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0039] Example 3: Ecological dihydrate gypsum-based waterproof inorganic water-based coating
[0040] Raw material ratio: 45 parts of dihydrate gypsum, 20 parts of metakaolin, 25 parts of white Portland cement, 4 parts of polyvinyl alcohol, 5 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0041] Example 4: Ecological dihydrate gypsum-based waterproof inorganic water-based coating
[0042] Raw material ratio: 30 parts of dihydrate gypsum, 15 parts of metakaolin, 35 parts of white Portland cement, 4 parts of polyvinyl alcohol, 15 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0043] Example 5: Ecological dihydrate gypsum-based waterproof inorganic water-based coating
[0044] Raw material ratio: 30 parts of dihydrate gypsum, 30 parts of metakaolin, 30 parts of white Portland cement, 4 parts of polyvinyl alcohol, 4 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0045] Example 6: Ecological dihydrate gypsum-based waterproof inorganic water-based coating
[0046] Raw material ratio: 30 parts of dihydrate gypsum, 20 parts of metakaolin, 20 parts of white Portland cement, 4 parts of polyvinyl alcohol, 25 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0047] Example 7: Ecological dihydrate gypsum-based waterproof inorganic water-based coating
[0048] Raw material ratio: 30 parts of dihydrate gypsum, 20 parts of metakaolin, 40 parts of white Portland cement, 4 parts of polyvinyl alcohol, 5 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0049] The coating raw material ratios of Examples 1-7 are used in the preparation of the following examples:
[0050] Example 8: Coating Preparation Method
[0051] Weigh the raw materials of each component, stir them evenly in a blender, and then pack them in a moisture-proof and sealed package to prepare the coating. (Note: Store in a dry and sealed environment.)
[0052] Example 9: Method of using coating
[0053] Add water to the coating prepared in Example 8 to adjust the viscosity of the slurry to 14-19s after applying 4 cups of the slurry. Stir evenly until there are no particles. Ensure that the material construction temperature is above 5°C. Wet the wall surface with clean water and then use it for brushing, rolling or spraying.
[0054] In order to further verify the feasibility and effectiveness of the present invention and screen out the best solution, the inventor conducted a series of experiments, as follows:
[0055] 1. Experimental Methods
[0056] 1. Technical indicators and test methods of coatings
[0057] According to the relevant technical indicators and test methods of "Inorganic Dry Powder Architectural Coatings" (JG / T 445-2014), the specific test items include: workability, coating appearance, flexibility, water resistance, alkali resistance, scrub resistance, temperature change resistance, stain resistance, resistance to artificial weathering, whiteness and pH. The test items and test standards / methods are as follows:
[0058] For construction performance, operability time and appearance test methods, refer to GB / T 9779-2015;
[0059] Drying time (surface drying) test method, refer to GB / T 1728;
[0060] Contrast ratio test method, refer to GB / T 23981;
[0061] Flexibility test method, refer to GB / T 1748;
[0062] Water resistance test method, refer to GB / T 1733;
[0063] Alkali resistance test method, refer to GB / T 9265;
[0064] The test method for scrub resistance is in accordance with GB / T 9266;
[0065] Temperature resistance test method, refer to GB / T9779;
[0066] The stain resistance test method refers to GB / T 9780;
[0067] Test method for resistance to artificial weathering, refer to GB / T 1865;
[0068] See Table 1-Table 2. Table 1 shows the technical performance requirements for inorganic dry powder exterior wall coatings in "Inorganic Dry Powder Architectural Coatings" (JG / T 445-2014). Table 2 shows the technical performance requirements for inorganic dry powder interior wall coatings in "Inorganic Dry Powder Architectural Coatings" (JG / T 445-2014).
[0069] Table 1 Technical performance requirements of inorganic dry powder exterior wall coatings
[0070]
[0071]
[0072] Table 2 Technical performance requirements of inorganic dry powder interior wall coatings
[0073]
[0074] 2 Test 1
[0075] 2.1 Raw material selection test, set up 7 recipes, the specific scheme is as follows:
[0076] Formula 1 - "Dihydrate gypsum is used as raw material"
[0077] Raw material ratio: 30 parts of dihydrate gypsum, 20 parts of metakaolin, 30 parts of white Portland cement, 4 parts of polyvinyl alcohol, 15 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0078] Formula 2 - "No dihydrate gypsum is used in the raw materials"
[0079] Raw material ratio: 20 parts of metakaolin, 30 parts of white Portland cement, 4 parts of polyvinyl alcohol, 45 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0080] Recipe 3 - "Use hemihydrate gypsum instead of dihydrate gypsum"
[0081] Raw material ratio: 30 parts of hemihydrate gypsum, 20 parts of metakaolin, 30 parts of white Portland cement, 4 parts of polyvinyl alcohol, 15 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0082] Recipe 4 - "Use anhydrous gypsum instead of dihydrate gypsum"
[0083] Raw material ratio: 30 parts of anhydrous gypsum, 20 parts of metakaolin, 30 parts of white Portland cement, 4 parts of polyvinyl alcohol, 15 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0084] Recipe 5: "No white Portland cement used in the raw materials"
[0085] Raw material ratio: 40 parts of dihydrate gypsum, 25 parts of metakaolin, 4 parts of polyvinyl alcohol, 30 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0086] Recipe 6: "No kaolin used in the raw materials"
[0087] Raw material ratio: 40 parts of dihydrate gypsum, 30 parts of white Portland cement, 4 parts of polyvinyl alcohol, 25 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0088] See Table 3.
[0089] Table 3 Coating formula screening table
[0090]
[0091]
[0092] 2.2. Preparation method:
[0093] Weigh the raw materials of the above components, stir them evenly in a blender, and then pack them in a moisture-proof and sealed package to prepare the coating. (Note: Store in a dry and sealed environment.)
[0094] 2.3 Performance test data and results:
[0095] The coatings prepared by formula 1-6 were subjected to performance testing under “1. Technical indicators and test methods of coatings” and the data obtained are shown in Table 4.
[0096] Table 4 Performance test data of dihydrate gypsum-based water-resistant powder type architectural coatings in embodiments and comparative examples
[0097]
[0098] From Table 4, we can see that:
[0099] The coating performance obtained by formula 1: the coating surface is flat and smooth, and there are no abnormalities in water resistance, alkali resistance, temperature change resistance, and artificial aging resistance. Other evaluation indicators meet the standards; the SEM image of the coating is shown in Figure 3 .
[0100] The coating performance obtained by formula 2: the coating surface is dry rubbed off powder, and the temperature-resistant part is damaged. Compared with formula 1, the construction performance of the product obtained in comparative example 2 is poor;
[0101] The coating performance obtained by formula 3: the coating surface is rough and uneven, and the stain resistance is 42.27%, which exceeds the technical indicators and is unqualified;
[0102] The coating performance obtained by formula 4: the coating surface is rough and uneven, and the stain resistance is 41.74%, which exceeds the technical indicators and is unqualified;
[0103] The coating properties obtained by formula 5: the coating surface is dry-rubbed and powdery, water resistance is damaged, alkali resistance is damaged, temperature resistance is often detached, and stain resistance is 37.38%, which exceeds the technical indicators and is unqualified;
[0104] The coating properties obtained by formula 6: the coating surface is dry-rubbed and powdery, water resistance is broken, alkali resistance is broken, temperature resistance often falls off, and stain resistance is 33.65%, which exceeds the technical indicators and is unqualified.
[0105] In summary, Formulation 1 is the preferred formulation.
[0106] 3 Test 2
[0107] 3.1 The optimal ratio screening test was carried out with the preferred formula 1 obtained under "2. Test 1", and 7 formulas were set up, as shown in Table 5.
[0108] Recipe A:
[0109] Raw material ratio: 30 parts of dihydrate gypsum, 20 parts of metakaolin, 30 parts of white Portland cement, 4 parts of polyvinyl alcohol, 15 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0110] The results are shown in Table 3, and the coating performance obtained is up to standard in all its evaluation indicators.
[0111] Recipe B:
[0112] Raw material ratio: 20 parts of dihydrate gypsum, 25 parts of metakaolin, 30 parts of white Portland cement, 4 parts of polyvinyl alcohol, 20 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0113] Recipe C:
[0114] Raw material ratio: 45 parts of dihydrate gypsum, 20 parts of metakaolin, 25 parts of white Portland cement, 4 parts of polyvinyl alcohol, 5 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0115] Recipe D:
[0116] Raw material ratio: 30 parts of dihydrate gypsum, 15 parts of metakaolin, 35 parts of white Portland cement, 4 parts of polyvinyl alcohol, 15 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0117] Recipe E:
[0118] Raw material ratio: 30 parts of dihydrate gypsum, 30 parts of metakaolin, 30 parts of white Portland cement, 4 parts of polyvinyl alcohol, 4 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0119] Recipe F:
[0120] Raw material ratio: 30 parts of dihydrate gypsum, 20 parts of metakaolin, 20 parts of white Portland cement, 4 parts of polyvinyl alcohol, 25 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0121] Recipe G:
[0122] Raw material ratio: 30 parts of dihydrate gypsum, 20 parts of metakaolin, 40 parts of white Portland cement, 4 parts of polyvinyl alcohol, 5 parts of quartz powder, 0.15 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retention agent.
[0123] Table 5 Coating formula screening table
[0124] raw material Recipe A Recipe B Recipe C Recipe D Formulation E Recipe F Formulation G Gypsum dihydrate(g) 30 20 45 30 30 30 30 Metakaolin(g) 20 25 20 15 30 20 20 White Portland Cement(g) 30 30 25 35 30 20 40 Polyvinyl alcohol (g) 4 4 4 4 4 4 4 Quartz powder(g) 15 20 5 15 5 25 5 Polycarboxylate high efficiency water reducing agent (g) 0.15 0.15 0.15 0.15 0.15 0.15 0.15 Defoaming agent(g) 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Dispersant(g) 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Leveling agent(g) 0.15 0.15 0.15 0.15 0.15 0.15 0.15 Anti-sagging agent(g) 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Water retaining agent (g) 0.1 0.1 0.1 0.1 0.1 0.1 0.1
[0125] 3.2 Preparation method:
[0126] Weigh the raw materials of the above components, stir them evenly in a blender, and then pack them in a moisture-proof and sealed package to prepare the coating. (Note: Store in a dry and sealed environment.)
[0127] 3.3 Performance test data and results:
[0128] The coating prepared by formula AG was subjected to performance testing under “1. Technical indicators and test methods of coating” and the data obtained are shown in Table 6.
[0129] Table 6 Performance test data of coatings prepared by formula AH
[0130]
[0131]
[0132] From the results in Table 6, it can be seen that the coating prepared by formula AG has a smooth surface, a dry time of less than 2 hours, a contrast ratio of 0.94-0.96, a washability of more than 2000 times, and a coating that is intact after 5 temperature-resistant cycles, a stain resistance of less than 15%, and meets the qualified requirements for water resistance, alkali resistance, and artificial weather aging resistance. The coating has a good appearance and no powdering, discoloration, or cracking. The pH of the coating slurry is 10, so no antibacterial agent needs to be added, and it also has an antibacterial effect. It will not mold or discolor when used on exterior walls. The whiteness is greater than 85, and no titanium dioxide pigment needs to be added, which can reduce costs.
[0133] Although the present invention has been described in detail above by means of general description, specific implementation methods and experiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. An ecological dihydrate gypsum-based waterproof inorganic water-based coating, characterized in that: The following raw materials are included by weight: 30 parts of dihydrate gypsum, 20 parts of metakaolin, 30 parts of white silicate cement, 4 parts of polymer powder binder, 15 parts of filler, 0.15 parts of high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.15 parts of leveling agent, 0.2 parts of anti-sagging agent, and 0.1 parts of water retaining agent; wherein the main component of the dihydrate gypsum is CaSO4·2H2O, with purity ≥90%, whiteness ≥80%, fineness ≥300 mesh, and moisture content ≤1%; the main components of the metakaolin are silicon dioxide and aluminum oxide, with whiteness ≥80%, fineness ≥500 mesh, and moisture content ≤1%; the fineness of the white silicate cement is ≥300 mesh, whiteness ≥80%, and moisture content ≤1%.
2. The ecological dihydrate gypsum-based waterproof inorganic water-based coating according to claim 1, characterized in that: The polymer powder binder is one or a combination of two or more of water-soluble polyvinyl alcohol, redispersible latex powder of vinyl acetate and ethylene copolymer, redispersible latex powder of ethylene, vinyl chloride and vinyl laurate terpolymer and redispersible latex powder of vinyl acetate, acrylate and higher fatty acid vinyl ester terpolymer; the fineness of the polymer powder binder is ≥100 mesh and the moisture content is ≤2%.
3. The ecological dihydrate gypsum-based waterproof inorganic water-based paint according to claim 1, characterized in that: The high-efficiency water reducing agent is a polycarboxylic acid high-efficiency water reducing agent; the defoaming agent is polyether modified silicon; the dispersing agent is polyethylene oxide; the leveling agent is polyether modified polydimethylsiloxane; the anti-sagging agent is polyamide wax powder; and the water retaining agent is hydroxypropyl methylcellulose.
4. The ecological dihydrate gypsum-based waterproof inorganic water-based paint according to claim 1, characterized in that: The filler is one or a combination of two or more of quartz powder, talcum powder, wollastonite powder, sericite powder, heavy calcium carbonate powder or diatomaceous earth powder, with a whiteness of ≥80%, a fineness of ≥600 meshes, and a moisture content of ≤1%.
Citation Information
Patent Citations
Wall coating composition capable of realizing inorganic film formation by using composite hydraulic-anhydraulic gel structure
CN111039643A
High-strength water-resistant plastering gypsum and producing method thereof
CN101265069A
Exciting agent for improving early performance of slag powder concrete by using desulfurization gypsum and preparation method of exciting agent
CN103241995A